Phylogeny and global diversity of Polyporus group Melanopus (Polyporales, Basidiomycota) - Dai, Yu Cheng (2014)
Polyporus accommodates species with stipitate basidiocarps, a dimitic hyphal system with skeleto-binding hyphae, and hyaline, thin-walled, more or less cylindrical basidiospores. The species of Polyporus are divided into six morphological groups, of which Melanopus is characterized by coriaceous basidiocarps, thin context and a black cuticle on the stipe. In this study, we explore the phylogeny and species diversity of Polyporus sensu lato focusing on the group Melanopus based on global samples. Our combined ITS and nLSU dataset included 117 collections represented by 117 ITS and 94 nLSU sequences, of which 43 ITS and 37 nLSU sequences were newly generated. The resulting phylogenetic analysis recovered four clades, Favolus, Neofavolus, Melanopus and Polyporellus clades, while several species in the morphological groups Melanopus and Polyporus were outside these clades. Combined with morphological evidence, three new species in the Melanopus clade, Polyporus americanus, P. austroandinus and P. conifericola, are newly described and illustrated, and their distinctive characters are discussed. The illegitimate name Polyporus fraxineus is renamed as Polyporus fraxinicola. The phylogeny and taxonomy of each species in group Melanopus (morphology) or Melanopus clade (phylogeny) and related species are briefly discussed.